Artificial Base-Directed In Vivo Formulation of Aptamer-Drug Conjugates with Albumin for Long Circulation and Targeted Delivery - Yang Sun; Xinyao Geng; Yue Ma; Yu Qin; Shangjiu Hu; Yuquan Xie; Ruowen Wang (MDPI AG, 2022)
Aptamer-drug conjugates (ApDCs) are potential targeted pharmaceutics, but their clinical applications are hampered by fast clearance in blood. Herein we report the construction of ApDCs modified with artificial base F and the study of biological activities. Two types of F-base-modified ApDCs were prepared, Sgc8-paclitaxel by conjugation and Sgc8-gemcitabine, by automated solid-phase synthesis. In vitro experiments showed that F-base-modified ApDCs retain the specificity of the aptamer to target cells and the biological stability is improved. In vivo studies demonstrated that the circulatory time is increased by up to 55 h or longer, as the incorporated F base leads to a stable ApDC-albumin complex as the formulation for targeted delivery. Moreover, conjugated drug molecules were released efficiently and the drug (paclitaxel) concentration in the tumor site was improved. The results demonstrate that an F-base-directed ApDC-albumin complex is a potential platform for drug delivery and targeted cancer therapy.